Model Persediaan Produk dan Bahan Kemasan Terintegrasi (Studi Kasus PT Indomex Dwijaya Lestari) - Nilda Tri Putri; Jonrinaldi -; Yohanna Safari (Performa: Media Ilmiah Teknik Industri, 2015)
One of the factors to increase the competitiveness is the price of product. One of the factors that affect the product price is inventory cost. Shortages inventory can result in the cessation of the production process so that inventory is one of crucial issue in the company's operation while overstock had an effect on high costs. This research aimed to obtain integrated inventory model between products and packaging materials to minimize the total cost of inventory at PT Indomex Dwijaya Lestari considering safety stock. Data used in this research are the major and minor setup cost, production cost (one cardboard products) , sales data of mineral water for cup and bottle products from January 2011-April 2013 , data of production bottle mineral water for cup and bottle products from January 2011-April 2013, and the price of packaging materials . Then, data is processed to obtain the minimum inventory cost by using a phased approach and the simultaneous approach (using the software LINGO 11.0) for inventory model that considers safety stock and inventory model without considering the safety stock.Results of this research obtained an integrated inventory model between products and packaging materials that considering safety stock and without considering safety stock in PT Indomex Dwijaya Lestari. Based on the calculation, the result is valid. The proposed inventory costs are cheaper than the company's current inventory costs. The cost of the company's current inventory is Rp. 15.020.370,09 considering safety stock per month . Inventory costs in the company without considering safety stock is Rp 13.651.301,74 per month. The cost of inventory using gradual approach is Rp. 4.328.441,38 per month considering safety stock and Rp. 2.745.085,15 per month without considering safety stock. The cost of inventory using the simultaneous approach is Rp. 3.543.637,00 per month considering safety stock and Rp. 3.543.637,00 per month without considering safety stock.